2011
DOI: 10.1007/s12020-011-9509-7
|View full text |Cite
|
Sign up to set email alerts
|

Urinary tubular biomarkers in short-term type 2 diabetes mellitus patients: a cross-sectional study

Abstract: The purpose of this study was to investigate the prevalence of tubular damage in short-term (less than five years) type 2 diabetes mellitus (T2DM) patients and to explore the correlation between tubular markers and their relationship with renal indices at different stages of diabetic nephropathy. A group of 101 short-term T2DM patients and 28 control subjects were recruited. Tubular markers, such as neutrophil gelatinase-associated lipocalin (NGAL), N-acetyl-β-D: -glucosaminidase (NAG), and kidney injury molec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
79
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 29 publications
15
79
1
4
Order By: Relevance
“…However, it has recently been pointed out that these markers have some drawbacks for predicting the renal outcome (3,4). With the aim of achieving more accurate prediction of the renal prognosis, other biomarkers have also been investigated, including markers of renal tubular injury and inflammation (3,5).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has recently been pointed out that these markers have some drawbacks for predicting the renal outcome (3,4). With the aim of achieving more accurate prediction of the renal prognosis, other biomarkers have also been investigated, including markers of renal tubular injury and inflammation (3,5).…”
Section: Introductionmentioning
confidence: 99%
“…An early study showed that urinary NAG and NGAL were significantly elevated in normoalbuminuric diabetic patients compared with nondiabetic healthy control and were associated with albuminuria and eGFR independent of age, sex and plasma concentrations of the respective biomarkers (Nauta et al 2011). Another recent cross-sectional study for the purpose of investigating the prevalence of tubular damage of type 2 diabetes showed that urinary NGAL was strongly positively correlated with the urinary albumin/creatinine ratio and negatively correlated with eGFR, where urinary KIM-1 showed no significant difference among the three diabetic subgroups (normoalbuminuria, microalbuminuria and overt proteinuria groups) but not correlated with albumin/creatinine ratio or eGFR (Fu et al 2012). An early study showed a stepwise increase in NAG concentration from normo-to micro-and macro-albuminuric patients (Piwowar et al 2006).…”
Section: Ngal Kim-1 and Nagmentioning
confidence: 97%
“…N-acetyl-β-D-glucosaminidase (NAG), an enzyme (MW 130kDa) involved in carbohydrate metabolism, plasma NAG can't be filtered through kidney and presence in urine is exclusively secreted by tubular cells lysosomes (Hong and Chia 1998). Urinary NGAL, KIM-1 and NAG in type 2 diabetic patients were markedly increased (Fu et al 2012). Urinary NGAL and KIM-1 were found to be upregulated in both type 1 diabetic patients with or without albuminuria and in type 2 diabetic patients in accordance with the decline in eGFR (Nielsen et al 2010, Nielsen et al 2012).…”
Section: Ngal Kim-1 and Nagmentioning
confidence: 99%
“…51 Fu et al also showed that urinary NGAL levels were elevated in a group of short-term type 2 DM patients (less than 5 years' duration) and that these levels showed a positive correlation with albuminuria and a negative correlation with estimated GFR, as compared with urinary kidney injury molecule 1 (KIM-1, see below). 52 These studies demonstrate that urinary NGAL may be an early marker of diabetic nephropathy, although prospective studies are lacking.…”
mentioning
confidence: 99%
“…51 In contrast with urinary NGAL, Fu et al showed that urinary KIM-1 did not show a correlation with albuminuria or estimated GFR in a group of short-term type 2 DM patients (less than 5 years' duration). 52 Thus, the prognostic value of KIM-1 for progression of diabetic nephropathy is debatable at this time. …”
mentioning
confidence: 99%